Polycyclic Aromatic Hydrocarbons Degradation by Aquatic Bacteria Isolated from Khazar Sea, the World's Largest Lake - Vida Ebrahimi; Shirin Eyvazi; Soheila Montazersaheb; Parivar Yazdani; Mohammad Amin Hejazi; Vahideh Tarhriz; Mohammad Saeid Hejazi (Tabriz University of Medical Sciences, 2021)
Background: Aquatic microorganisms have an important role in the bioremediation of environmental pollutants. Polycyclic Aromatic Hydrocarbons (PAHs) are described as dangerous pollutants that can bind covalently to the nucleic acids, causing mutations. Therefore, they have carcinogenic and toxic properties. Also, are involved in diseases such as asthma, lung dysfunction, and chronic bronchitis. This study aimed to isolate and characterize aquatic bio-degrading bacteria from the world's largest lake, Khazar, with the ability to use PAHs as only carbon source. Methods: Samples were taken from the estuary of Siah Rud River (Mazandaran province, Iran) and Fereydunkenar beach leading to isolation of twenty-three bacteria on marine agar and sea water media. The isolates were cultured on separate ONR7a medium, each supplemented with only one PAH; as the sole carbon source; including naphthalene, phenanthrene, and anthracene. Results: Eleven bacterial isolates were able to grow on supplemented media: TBZ-E1, TBZ-E2, TBZ-E3, TBZ-S12, TBZ-S16, TBZ-E20, TBZ-SF2, TBZ-F1, TBZ-F2, TBZ-F3 and TBZ2. These isolates belong to Alteromonas, Marivivens, Pseudoalteromonas, Vibrio, Shewanella, Photobacterium, Mycobacterium and Pseudomonas genera. The qualitative analysis showed that the consortium of isolates TBZ-F1, TBZ-F2, TBZ-F3, TBZ-SF2, and TBZ2 displayed the highest degradation rate for phenanthrene and naphthalene. Naphthalene, phenanthrene, and anthracene were potently degraded by TBZ2 and TBZ-SF2 and accordingly were subjected to measure degradation potential of mentioned PAHs. Conclusion: The bacterial isolates of Caspian lake have a critical duty in biodegradation of PAHs. These isolates are representative samples of the bacterial population of this lake, participating in the purification process of this habitat.